Talent management in higher education - Thunnissen, Marian; Boselie, Paul (Talent management (Emerald Publishing), 2024)
The ebook edition of this title is Open Access and freely available to read online.  Despite the enormous expansion of research on Talent Management (TM), a degree of ambiguity about definitions and conceptual boundaries remains, and there is little attention for how TM is actually conceived, implemented and developed within organizations. This short book aims to present an overview of empirical research on TM, and offers an integrated model that addresses the full nature and scope of TM in practice. This book will provide a comprehensive overview of and introduction to the current state of the talent management field, for both an academic and practitioner audience. From this point, the authors intend to introduce a talent management framework that can be easily implemented and it is this that will provide the most impactful takeaway from the book.